The problem of electrical injury during the operation of electrical installations in underground workings of iron-ore mines - Синчук, Олег Николаевич; Харитонов, Александр Александрович (Eastern-European Journal of Enterprise Technologies, 2014)
A safety state assessment in the application of electrical power at mining enterprises is given in the research materials. A prevention assessment of electrical injury state in domestic mining industry is given, and the basic data on the classification of electrical injury causes and the study of electrical injury emergence in the mining industry are presented. In accordance with the target goal the issues for further studies on the preparation of managed decisions on electrical injury prevention are given. The analysis of electrical injury specifics in the mining works shows the need for a more thorough study of the causes of its emergence on the basis of the studies of factors influence, involved in the formation of electrical injury-risk situations and negative effects on the reliability of electrical equipment and electrical means. These studies should be the basis for developing a set of preventive measures aimed at effective reduction of electrical injury. The justification and development of methodological principles of identifying the cause-and-effect relations of the system "man - environment - electrical installation" in the direction of electrical injury emergence in the system "man - iron ore production - electrical systems" will allow to prepare managed decisions on electrical injury prevention in the mining industry. The research results will allow to develop measures to improve the safety of electrotechnical complexes and the systems of mining enterprises, and in this case specifically in iron-ore mines.